2010
DOI: 10.1007/s00216-010-3890-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of ε-caprolactone polymerization by NIR spectroscopy

Abstract: Near-infrared (NIR) spectroscopy is proposed for the in-line quantitative and kinetic study of the polymerization of epsilon-caprolactone and eventually to facilitate real-time control of the manufacturing process. Spectra were acquired with a fibre-optic probe operating in transflectance mode immersed in the reactor. The NIR data acquired were processed using a multivariate curve resolution alternating least squares (MCR-ALS) algorithm. The proposed method allows calculation of the concentration and spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…7 In particular, it is used for in-line monitoring of various polymerization reactions. In most cases, the progress of batch polymerization processes was followed, [8][9][10][11][12][13] but also the photopolymerization of thin coatings of acrylates and epoxies has been monitored by this method. [14][15][16] Currently, ultraviolet (UV) curing of functional coatings is a rapidly growing technology.…”
Section: Introductionmentioning
confidence: 99%
“…7 In particular, it is used for in-line monitoring of various polymerization reactions. In most cases, the progress of batch polymerization processes was followed, [8][9][10][11][12][13] but also the photopolymerization of thin coatings of acrylates and epoxies has been monitored by this method. [14][15][16] Currently, ultraviolet (UV) curing of functional coatings is a rapidly growing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several applications involved batch polymerization processes monitored in the reactor by NIR. MCR using ALS applied to NIR spectra was used to calculate the concentrations and spectral profiles of species involved in the polymerization reaction of ε-caprolactone . Although concentrations of these species could not be provided for MCR, it was possible to compute the concentrations because the spectral matrix was extended using both process and pure analyte spectral to address the problem of rank deficiency.…”
Section: Process Chemometricsmentioning
confidence: 99%
“…MCR using ALS applied to NIR spectra was used to calculate the concentrations and spectral profiles of species involved in the polymerization reaction of ε-caprolactone. 187 Although concentrations of these species could not be provided for MCR, it was possible to compute the concentrations because the spectral matrix was extended using both process and pure analyte spectral to address the problem of rank deficiency. Kinetic information about the reaction (activation energy and rate constants) could be collected from the data which was obtained from a fiber optic probe of the NIR spectrometer which was inserted into the reactor.…”
Section: ' Process Chemometricsmentioning
confidence: 99%
“…Owing to the enormous capability of NIR spectroscopy assisted by chemometrics, this spectroscopy has found numerous applications in process and routine quality control in quite different areas, ,, for example, in waste sorting , and in agriculture as well as in the food, petrochemical, , polymer, pharmaceutical, and biochemical sectors . More recently, it has been shown that NIR reflection spectroscopy can be also used for the in-line characterization of thin polymer layers.…”
Section: Introductionmentioning
confidence: 99%